Qingxuan Jiangya Decoction Reverses Vascular Remodeling by Inducing Vascular Smooth Muscle Cell Proliferation in Spontaneously Hypertensive Rats - Jianfeng CHU; Fei XIAO; Meiling YANG; Yang FU; Feng ZHENG; Jun PENG (康复学报)
Objective:To discuss the therapeutical effect of Qingxuan Jiangya decoction (QXJYD) on spontaneously hypertensive rats (SHR).Methods:By using SHR as hypertension model, rats were randomized into two groups: SHR+QXJYD group and SHR group, and ten Wistar-Kyoto rats were set as WKY group. During experimental period systolic blood pressure (SBP) and body weight were measured weekly. After eight weeks with the treatment of QXJYD, the aortas tissue was collected for histopathologic examination. The media thickness (MT) and lumen diameter (LD) were measured, ratio of lumen diameter/media thickness (LD/MT) in the carotid arteries were calculated, the gene and protein expression levels of Bax and Bcl-2 were detected.Results:SBP in SHR+QXJYD group was obviously lower than that in SHR group (P<0.05). QXJYD significantly decreased MT and ratio of LD/MT in the carotid arteries (P<0.05). QXJYD could markedly reverse vascular remodeling, and had no significant influence on lumen diameter of artery (P>0.05). A significant reduced expression of anti-apoptotic Bcl-2 proteins and ratio of Bcl-2/Bax were found in SHR+QXJYD group compared with those in SHR group (P<0.05).Conclusion:QXJYD can reverse vascular remodeling by controlling the blood pressure of SHR and inducing proliferation of vascular smooth muscle cells (VSMCs) in vivo.